TOTAL AND DIFFERENTIAL LEUKOCYTES OF LAYING CHICKENS AFTER NEWCASTLE DISEASE AND INFECTIOUS BRONCHITIS VACCINATION - Iqbal Bayu Samudra; Anak Agung Sagung Kendran; Gusti Ayu Yuniati Kencana; I Made Damriyasa; Ida Bagus Kade Suardana; I Gede Soma (Buletin Veteriner Udayana, 2024)
Research on the total and differential leukocytes of post-vaccination laying hens which was carried out on commercial farms in Tabanan Regency, Bali aims to determine and study the effect of combination vaccines Newcastle Disease LaSota strains and Infectious Bronchitis on the total number and types of leukocytes in the blood. A total of 40 laying hens aged 30 weeks were taken using purposive sampling for the research sample. Chicken blood samples were taken four times, starting from pre-vaccination to three weeks post-vaccination. The total leukocyte count is checked using a hemocytometer, while the leukocyte differential is checked using a blood smear. Data from total and differential leukocyte examination results were analyzed quantitatively descriptively. The results showed that there was a significant effect (p<0.05) on total leukocytes, heterophils, eosinophils and lymphocytes, and no significant effect (p>0.05) on basophils and monocytes.